PELATIHAN DAN PENDAMPINGAN DASAR PEMROGRAMAN MATLAB (MATRIX LABORATORY) DI SMK PGRI BANJARBARU - Trianiza, Ice; Abdurrahim sidiq; Ayu Novia Lisdawati (Yayasan Sagita Akademia Maju, 2023)
SMK PGRI BANJARBARU is one of the private schools located on the Loktabat rubber plantation road, Banjarbaru City which has quite good resources, both teachers, staff and students. At this time, the knowledge regarding mathematical programming for teachers and students at SMK PGRI BANJARBARU is only limited to learning knowledge, without any skills, for this reason it is necessary to provide training and mentoring in mathematical programming, one of which is using MATLAB software, which must make programming material an open material. given to the students. Programming languages taught. teachers to students now are HTML and JavaScript. Then, the school switched to Pascal recently, but there are no reports regarding student performance. Based on information and requests from the Principal, Mr. Setiawan S.E, during a field study visit in February 2023, asked the proposing team to provide Matlab programming training for students and teachers at his school. A preliminary survey has also been carried out by the implementing team at this school. This school has provided electricity facilities and has a number of computers. This really supports the implementation of the activities in question. This is what underlies us to carry out community service with the title Basic training and assistance for programming matlab teachers at SMK PGRI BANJARBARU. The results of knowledge regarding Matlab training and assistance increased as seen by the students' average score of 92.5